Pemberdayaan Karang Taruna dalam Sirkular Ekonomi Pengelolaan Sampah dan Pertanian Organik Skala Rumah Tangga - Pasasa, Linus; Singarimbun, Alamta; Parnadi, Wahyudi (MJI Publisher by PT Mitra Jurnal Indonesia, 2025)
This community service program aims to empower local community partnerships by equipping residents with knowledge and problem-solving skills that are comprehensive, meaningful, thorough, and sustainable. It does so through the application of the circular economy concept, which seeks to extend the life cycle of products, raw materials, and available resources so that they can be used for as long as possible. This concept emphasizes the importance of conserving resources by reducing waste and recycling materials after their use, thereby creating a sustainable loop. It is an innovative approach that not only has the potential to reduce negative environmental impacts but also opens new economic opportunities through the development of sustainable businesses. The target partner of this program is the economically unproductive youth community group Karang Taruna PAKUPAYUNG, located in Pasirlayung Urban Village, Cibeunying Kidul District, Bandung City. The objective of this community engagement initiative is to empower Karang Taruna PAKUPAYUNG by utilizing plastic recycling within the framework of a circular economy in household-scale waste management and organic farming. The ultimate goal is to achieve zero waste and support food security in the Pasirlayung community. The results of the analysis indicate a significant increase in knowledge among the Karang Taruna PAKUPAYUNG members regarding